KOREOGRAFI MARAJUIK ASA: INTERPRETASI ATAS TARI PIRING DEBUS ANDALEH, TANAH DATAR - Yeni Eliza; Rasmida Rasmida; Susas Rita Loravianti (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT Women have an important role in rumah gadang. Meanwhile, men generally live in surau to learn Qur’an and study traditional arts. The tradition shifts because of the influence of current development that results on traditional arts are no longer inherited to the young generation. In this writing, it is described the method of work creation started from the stages of contemplation, observation, data collection, interview, elaboration, synthesis, realization, until completion in the form of artwork performance. Therefore, the objective of this work creation is achieved namely traditional art particularly Piring Debus dance becomes popular and people feel that traditional art belongs to them. Keywords: Revitalization, Art, Tradition